TRiC/CCT Complex, a Binding Partner of NS1 Protein, Supports the Replication of Zika Virus in Both Mammalians and Mosquitoes - Wang, Yuchen (Viruses, 2020)
Mosquito-borne Zika virus (ZIKV) can cause congenital microcephaly and Guillain–Barré syndrome, among other symptoms. Specific treatments and vaccines for ZIKV are not currently available. To further understand the host factors that support ZIKV replication, we used mass spectrometry to characterize mammalian proteins that associate with the ZIKV NS1 protein and identified the TRiC/CCT complex as an interacting partner. Furthermore, the suppression of CCT2, one of the critical components of the TRiC/CCT complex, inhibited ZIKV replication in both mammalian cells and mosquitoes. These results highlight an important role for the TRiC/CCT complex in ZIKV infection, suggesting that the TRiC/CCT complex may be a promising therapeutic target.